MILP model for resource disruption in parallel processor system - Nordin, Syarifah; Caccetta, Louis (AIP Publishing, 2015)
In this paper, we consider the existence of disruption on unrelated parallel processor scheduling system. The disruption occurs due to a resource shortage where one of the parallel processors is facing breakdown problem during the task allocation, which give impact to the initial scheduling plan. Our objective is to reschedule the original unrelated parallel processor scheduling after the resource disruption that minimizes the makespan. A mixed integer linear programming model is presented for the recovery scheduling that considers the post-disruption policy. We conduct a computational experiment with different stopping time limit to see the performance of the model by using CPLEX 12.1solver in AIMMS 3.10 software.